Lessons from using qualitative methods in the Project-Level Women's Empowerment in Agriculture Index (pro-WEAI) - Rubin, Deborah S.; Myers, Emily; Meinzen-Dick, Ruth S. (CGIAR GENDER Impact Platform, 2022)
The Women’s Empowerment in Agriculture Index (WEAI), launched in 2012, and its later iterations, including the project-level WEAI (pro-WEAI), have become well-known standards for measuring shifts in women’s and men’s empowerment. Less well recognized is how the surveys have benefitted from qualitative research and its ability to provide insights into peoples’ perceptions and beliefs, in their own words, helping to clarify the reasons behind their behaviors.